2022
DOI: 10.1039/d1sm01680f
|View full text |Cite
|
Sign up to set email alerts
|

Metachronal patterns by magnetically-programmable artificial cilia surfaces for low Reynolds number fluid transport and mixing

Abstract: Motile cilia can produce net fluid flows at low Reynolds number because of their asymmetric motion and metachrony of collective beating. Mimicking this with artificial cilia can find application in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…5B (ii). Such enhancement to fluid transportation by producing metachronal waves in the array direction is also observed in cilia arrays at low Reynolds numbers through numerical investigation ( 33 ).…”
Section: Resultsmentioning
confidence: 74%
“…5B (ii). Such enhancement to fluid transportation by producing metachronal waves in the array direction is also observed in cilia arrays at low Reynolds numbers through numerical investigation ( 33 ).…”
Section: Resultsmentioning
confidence: 74%
“…Figure 6A shows that both synchronous and dexioplectic motion could generate translational flows while laeoplectic motion only induced local chaotic flows. This is probably caused by the so-called shielding effect of neighboring cilia: The flow induced by each cilium is obstructed by the neighboring cilia ( 20 , 24 , 63 ). The F-MAC with a laeoplectic metachrony shows larger intercilia shielding effect, which leads to local chaotic flows indicated by the chaotic movement of the tracer particles ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The magnetic couples τ were due to the MAC magnetization m and the externally applied rotating magnetic field ( B ) by using τ = m × B . More details on the numerical model can be found in our previous work ( 54 , 63 ). The geometry and the magnetic and mechanical properties of the MAC were taken directly from the experimental results.…”
Section: Methodsmentioning
confidence: 99%
“…In Stokes flow conditions (), recent studies have identified a ciliary ‘shielding effect’ in which the flow generated by a beating cilium is obstructed by adjacent cilia (Khaderi, Den Toonder & Onck 2011; Milana et al. 2020; Zhang, den Toonder & Onck 2021, 2022). This effect is present throughout the entire beating cycle, but it is especially pronounced during the recovery stroke, leading to an overall increase in net flow.…”
Section: Resultsmentioning
confidence: 99%